An investigation on the effect of PCM incorporation in refrigerator through CFD simulation. (2021) - Pavithran, Anand; Sharma, Meeta; Shukla, Anoop Kumar
Abstract: In this current era almost every household utilizes at least one refrigerator for store and preserve the food materials. Refrigerators consume a considerable amount of electricity in the domestic sector because of their wide and continuous usage. Many approaches have been introduced to reduce electrical energy consumption by the refrigerator systems. Among those approaches, Phase Change Material (PCM) incorporation in refrigerators is a novel approach. The PCM materials are capable store and discharge a huge amount of thermal energy by changing its phase from solid to liquid and vice versa. During the compressor on-mode the incorporated PCM will store the cold energy by changing its phase from liquid to solid and in the period of compressor off-mode the PCM release the cold energy and maintain the temperature inside the system until the PCM melts completely. This procedure improves the compressor off-time period and which leads to a reduction in energy consumption. This research work focusing on the numerical simulation of PCM incorporated refrigerator. The CFD simulation methodology was taken to predict the results. The objective of the work is to analyze the effect of PCM incorporation in the refrigerator, for that different configuration arrangement of PCM in refrigerators are taken for this study. The simulation works are conducted by using ANSYS fluent software. The CFD simulation results indicate that the PCM incorporation in refrigerator is a promising technique for temperature maintenance during compressor off-mode. Moreover, it is also be noted that the area coverage and the configurations arrangement of PCM are significantly affecting the temperature maintenance inside the system.